Reverse shoulder arthroplasty used for revision of reverse shoulder arthroplasty: a systematic review - John J. Heifner, MD, MS; Anjali D. Kumar, MPH; Eric R. Wagner, MD, MS (JSES Reviews, Reports, and Techniques, 2021)
Background: As reverse shoulder arthroplasty (RSA) cases increase, so too will the need to revise subsequent failures. Many of the complications associated with revising anatomic total shoulder and hemiarthroplasty have been adequately addressed by RSA including glenoid bone deficiency, instability, and functional outcomes. However, the risk for complication when revising a failed reverse prosthesis may be more pronounced with increased bone and soft tissue deficiency. The ability for the reversed prosthesis to accommodate these insufficiencies following a prior reversed prosthesis is unclear. Methods: PubMed, Embase, and Google Scholar were queried for articles which fit the inclusion criteria of a reversed prosthesis used to revise a failed primary reverse prosthesis with a minimum follow-up of 12 months and clinical outcome reporting. Results: After exclusions, 9 studies reporting on 242 reverse shoulders with a mean follow-up of 40.29 months were analyzed. The differences between preoperative and postoperative weighted means were not significant for Constant (P = .26), American Shoulder and Elbow Surgeons Shoulder score (P = .61), SSV (P = .57), and visual analog scale for pain (P = .48). Functional improvements in elevation (74°-102°) and external rotation (18°-21°) were consistent with those reported for primary reverse procedures, although differences in preoperative and postoperative measures were not statistically significant. Patient satisfaction was 89% with a major complication rate of 25%. Discussion: The reverse shoulder prosthesis has proven satisfactory in revising hemiarthroplasty and anatomic total shoulder arthroplasty. The current results indicate RSA is also a satisfactory treatment option when revising a prior reverse prosthesis. Inherent to revision shoulder surgery is the obstacle of humeral and glenoid bone loss, an attenuated soft-tissue envelope, and instability. The reverse prosthesis may adequately address these commonly confronted difficulties with its inherent design characteristics. RSA provides a secure glenoid fixation for bone grafting, the ability to increase construct stability with component sizing, and a reliance on the deltoid for function. As our learning about revision of RSA improves, so will our ability to preemptively address potential issues which may lead to decreased complications in these cases. Despite the 25% rate of major complication, patients reported satisfaction of 89% which demonstrates the improvements in function and pain relief that are provided by the reverse prosthesis.